English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

please help

2006-12-26 12:05:33 · 4 answers · asked by dell10314 1 in Science & Mathematics Mathematics

4 answers

3 cos^2(x+1)*(-sin(x+1))

2006-12-26 12:07:49 · answer #1 · answered by raj 7 · 1 0

This is by general power rule:
Bring down the power, subtract one from the power and multiply by the derivative of the inside function.

3 cos^2(x+1) * - sin(x+1)

= -3 cos^2(x+1) sin(x+1)

2006-12-26 21:07:23 · answer #2 · answered by Professor Maddie 4 · 1 0

Use the chain rule:

du^3/du = 3u² (u is cos)

dcos u/du = -sin u (u is x+1)

d(x+1)/dx = 1

then put them together:

3cos² (x+1) • -sin (x+1) • 1 =
-3cos² (x+1) sin (x+1)

2006-12-26 20:14:59 · answer #3 · answered by Philo 7 · 1 0

dy/dx cos^3(x+1)
u = x +1
du/dx = 1
dv/du = -sin(x+1)
dy/dv = 3cos^2(x+1)

dy/dx = 3cos^2(x+1) X -sin(x+1)

2006-12-26 21:21:41 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers